Consumption Patterns and Distribution of Household Income Recipients of PKH (Program Keluarga Harapan) in Jiken Village, Jiken District, Blora District - Mulyono, Deva Damayanti; Arif, Muhammad (Prosiding University Research Colloquium, 2022)
The purpose of this study was to determine the consumption pattern and income distribution of PKH beneficiaries in Jiken Village, Jiken District, Blora District. The research method used is descriptive qualitative, with a research focus on household consumption patterns. The number of samples is 72 housewives who receive PKH. Methods of data collection is done by interview, observation, and documentation. The data analysis technique was carried out using the Gini coefficient to calculate the inequality of income distribution. The resource persons are dominated by housewives with an age range of 40-50 and low education. The results showed that the pattern of household consumption was divided into food and non-food consumption, non-food consumption was higher. The highest non-food consumption is the allocation of income to buy cigarettes. Income distribution is included in the category of low inequality. The PKH program really helps the household economy and the presence of PKH assistants has a very high impact on the distribution of aid and suppresses social jealousy. A good poverty alleviation program is that poverty data is mature, there is a commitment between the facilitator and recipient of assistance to tell the real condition.